Clays and Clay Minerals, Vol. 57, No. 6, 706–714, 2009. - Szabo, Tamas; Wang, Jun; Volodin, Alexander; Van Haesendonck, Chris; Dekany, Imre; Schoonheydt, Robert A. (My University, 2009)
The sizes and shapes of single clay mineral layers are difficult to determine though they are important parameters which determine the final properties of clay polymer nanocomposites and of ultrathin clay mineral films. To determine these sizes and shapes, hybrid monolayers of clay minerals (saponite, hectorite, Wyoming bentonite, and Laponite) and Rhodamine B octadecyl ester perchlorate (RhB18) were prepared using the Langmuir-Blodgett (LB) technique and studied with atomic force microscopy (AFM). The AFM images reveal monolayers of elementary clay mineral layers, which are randomly oriented and have a wide range of sizes. The layers have typical shapes: lath-like for hectorite, plates for Wyoming bentonite, a mixture of laths and plates for saponite, and aggregates of very small layers of Laponite. Two types of layers were present in the LB films of saponite,Wyoming bentonite, and hectorite in a 40:60 ratio: (1) single layers 0.96 nm thick hybridized with RhB18; and (2) particles consisting of two clay layers with an intercalated monomolecular layer of water molecules and hybridized with RhB18. The Laponite particles in the hybrid LB films consist mainly of aggregates of two and three single layers.
Afm Study Of Smectites In Hybrid Langmuir-blodgett Films: saponite, Wyoming Bentonite, Hectorite, And Laponite
gsccm57604-sza.pdf- 880KB
Keywords: Periodicals; Geology; AFM; Hectorite; Laponite; Saponite; Wyoming Bentonite